A palladium nanoparticle-catalyzed aryl–amine coupling reaction: high performance of aryl and pyridyl chlorides as the coupling partner. (18th December 2017) - Nandi, Debkumar; Islam, Rafique Ul; Devi, Nishu; Siwal, Samarjeet; Mallick, Kaushik
Abstract : A carbon nitride-supported Pd nanoparticle-catalyzed C–N cross coupling reaction. Abstract : Carbon nitride (CN)-supported nanosized palladium particles, Pd–CN, have been found to be an active catalyst system for the amination of aryl and pyridyl chloride moieties in the presence of dialkyl amine under mild reaction conditions. The recyclability study of the reaction shows the stable performance of the catalyst without a significant loss of catalytic activity for a couple of cycles.